College Students' Readiness for Online Learning: An Exploratory Study - Fitri Endang Srimulat; Jailani Syahputra Siregar; Syahrul Budiman; Maisaroh Ritonga; Ruwaidah Ruwaidah (Universitas Pahlawan Tuanku Tambusai, 2022)
Universities make several alterations to their educational programs in order to generate high-quality graduates. One is a shift away from traditional blended learning toward entirely online learning. Universities must begin preparing students for online education, particularly in the event of a pandemic. The student's readiness to study is critical to the success of online education. The goal of this study was to determine students' readiness to pursue higher education online. A Google form was used to deliver an online questionnaire to 473 students at Al Washliyah University Labuhanbatu. Online Student Learning Readiness scores for students at Al Washliyah University Labuhanbatu averaged 69 percent. With an 88.9 percent readiness rating, social competency is the most critical criterion. Based on these variables, one may conclude that students can efficiently socialize with their classmates while studying online.